Treatment Combinations: The Joint Effects of Multiple Evidence-Based Interventions on Recidivism Reduction - Hsieh, Ming-Li (Criminal justice and behavior, 2022)
Evidence-based interventions have been implemented within penal institutions to reduce the propensity of postrelease reoffending across states. Traditional program evaluations explore these interventions and demonstrate treatment effects most often for a single specific intervention. Although this process supports the doctrine of evidence-based research, little is known of the joint effects of multiple program assignments. The current study examines the treatment effects of sequence combinations of institutional programs on recidivism outcomes. Results demonstrate that correctional clients experienced incremental improvements when receiving more than two interventions compared with those who participated in a standalone intervention. Those who participated in three types of treatment combinations consisting of basic skills, vocational training, and cognitive behavioral treatment were more likely to reduce postrelease reconvictions.